2006
DOI: 10.2337/diabetes.55.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer T-Cells Participate in Rejection of Islet Allografts in the Liver of Mice

Abstract: A role of natural killer T (NKT) cells in transplant rejection remains unknown. Here, we determined whether NKT cells participate in rejection of islet allografts, using NKT cell-deficient mice. Survival of islet allografts in streptozotocin-induced diabetic CD1d ؊/؊ mice or V␣14 NKT cell ؊/؊ mice was significantly prolonged without immunosuppression when grafted into the liver, but not beneath the kidney capsule, compared with wild-type mice. Acceptance of intrahepatic islet allografts was achieved in CD1d ؊/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…These results could be explained by the preferential homing of Th1-inducing iNK T subpopulations towards atheromatous lesions in this particular animal model, as it was reported to be due to interferon (IFN)-g secretion [28]. Also, iNK T cells have been shown to mediate allograft rejection, but without distinction regarding the iNK T subpopulations involved [29]. Interestingly, similar to our results in stable cardiac allograft recipients, a previous study has shown a decreased proportion of circulating iNK T levels as well as of the CD4 + iNK T cell subset in stable renal transplant recipients [30].…”
Section: Treg and Inkt Cells In Allograft Recipientsmentioning
confidence: 93%
“…These results could be explained by the preferential homing of Th1-inducing iNK T subpopulations towards atheromatous lesions in this particular animal model, as it was reported to be due to interferon (IFN)-g secretion [28]. Also, iNK T cells have been shown to mediate allograft rejection, but without distinction regarding the iNK T subpopulations involved [29]. Interestingly, similar to our results in stable cardiac allograft recipients, a previous study has shown a decreased proportion of circulating iNK T levels as well as of the CD4 + iNK T cell subset in stable renal transplant recipients [30].…”
Section: Treg and Inkt Cells In Allograft Recipientsmentioning
confidence: 93%
“…The liver as transplantation side is considered to be a major contributor to these low success rates. Inadequate revascularization,5 the large numbers of natural killer T cells in the liver,6 high concentrations of immunosuppressive drugs,7, 8 and the instant blood‐mediated inflammatory reaction9 play a role in islet graft failure after intraportal transplantation. Therefore, a more adequate transplantation site is required for this technology to gain widespread acceptance and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Sirolimus doses of 2-6 mg/kg/day provided maximum graft survival in the heterotopic heart allograft model, 26 and intraperitoneal doses as high as 24 mg/kg have been used to induce tolerance to skin allograft in mice. 27,28 The tacrolimus dose employed by us (6 mg/kg) was also near or within the range that has been used in experimental models of allograft rejection [29][30][31] or of the injury induced after reperfusion 32 or partial hepatectomy. 33 In addition, some studies suggest that a higher than usual dose of tacrolimus is required for inhibiting the innate cell-mediated immune response, and doses of 10 mg/kg/day have been used in mice for this purpose.…”
Section: Discussionmentioning
confidence: 99%